Taman Gizi Sebagai Upaya Pemanfaatan Lahan Di Desa Loru - Zindy Kaludia; Betty Betty; Adfiyani Fadjar (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2023)
Empowering the community's economy by implementing a community-based nutritional garden program with the aim of cultivating yards, adding nutrition, and increasing family income growth. Methods The implementation of the activity begins with coordinating with village officials, then socializing the community's economic empowerment, then planting horticultural crops, namely kale, spinach, ginger, and turmeric. This activity took place in Loru Village, Biromaru District, Sigi Regency, Central Sulawesi. The results of this activity are able to provide motivation for some people to start living a healthy and clean life, utilize the land and can help the economic growth of the people of Loru Village. family income. Methods The implementation of the activity begins with coordinating with village officials, then socializing the community's economic empowerment, then planting horticultural crops, namely kale, spinach, ginger, and turmeric. This activity took place in Loru Village, Biromaru District, Sigi Regency, Central Sulawesi. The results of this activity are able to provide motivation for some people to start living a healthy and clean life, utilize land and can help the economic growth of the people of Loru Village.